Lesional senescent CD4+ T cells mediate bystander cytolysis and contribute to the skin pathology of human cutaneous leishmaniasis - Covre, Luciana Polaco; Fantecelle, Carlos Henrique; Garcia de Moura, Renan; Oliveira Lopes, Paola; Sarmento, Isabela Valim; Freire-de-Lima, Celio Geraldo; Decote-Ricardo, Debora; de Matos Guedes, Herbert Leonel; da Fonsceca-Martins, Alessandra Marcia; de Carvalho, Lucas Pedreira; de Carvalho, Edgar Marcelino; Mosser, David M.; et al. (Frontiers in Immunology, 2024)
Cytotoxic activity is a hallmark of the immunopathogenesis in human cutaneous leishmaniasis (CL). In this study, we identified accumulation of CD4 + granzyme B producing T cells with increased cytotoxic capacity in CL lesions. These cells showed enhanced expression of activating NK receptors (NKG2D and NKG2C), diminished expression of inhibitory NKG2A, along with the upregulation of the senescence marker CD57. Notably, CD4 + T cells freshly isolated from CL lesions demonstrated remarkable capacity to mediate NL-like bystander cytolysis. Phenotypic analyses revealed that lesional CD4 + T cells are mainly composed of latedifferentiated effector (CD27-CD45RA-) and terminally differentiated (senescent) TEMRA (CD27-CD45RA+) subsets. Interestingly, the TEMRA CD4 + T cells exhibited higher expression of granzyme B and CD107a. Collectively, our results provide the first evidence that senescent cytotoxic CD4 + T cells may support the skin pathology of human cutaneous leishmaniasis and, together with our previous findings, support the notion that multiple subsets of cytotoxic senescent cells may be involved in inducing the skin lesions in these patients.